2015
DOI: 10.1080/14763141.2015.1024277
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical interactions between an American football cleat and playing surfacesin-situat loads and rates generated by elite athletes: a comparison of playing surfaces

Abstract: This study quantified the mechanical interactions between an American football cleat and eight surfaces used by professional American football teams. Loading conditions were applied with a custom-built testing apparatus designed to represent play-relevant maneuvers of elite athletes. Two natural grass and six infill artificial surfaces were tested with the cleated portion of a shoe intended for use on either surface type. In translation tests with a 2. 8-kN vertical load, the grass surfaces limited the horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…The difference in relative velocity and acceleration amplitude between the two outcomes in measured data ( Fig. 5C,D ) was probably derived from the attacker’s prediction to avoid bumping into the defender after the attacker’s prediction to fail in attack 24 , rather than from competition dynamics of the one attractor and divergence from the attractor. Specifically in determination phase to determine the outcome (see Methods and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The difference in relative velocity and acceleration amplitude between the two outcomes in measured data ( Fig. 5C,D ) was probably derived from the attacker’s prediction to avoid bumping into the defender after the attacker’s prediction to fail in attack 24 , rather than from competition dynamics of the one attractor and divergence from the attractor. Specifically in determination phase to determine the outcome (see Methods and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two competitive agents should abruptly change the whole two-agent system to achieve their objectives (e.g. escape 23 or attack 24 ) from the deadlock or skirmish situations which have been revealed in tag-play 21 and martial arts 20 22 . Nonlinear dynamics have also investigated bifurcation phenomena defined as discontinuous qualitative changes in a system caused by the continuous change of some control parameter (bifurcation parameters) 25 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Foot and Ankle Subcommittee has performed multiple studies examining the mechanical interaction between football cleats and playing surfaces, 30 foot kinematics and loading during various football-specific tasks, 31 and the biomechanics of metatarsophalangeal joint ("turf toe") injuries. 32 This last example illustrates the practical application of their in vitro research that showed that most turf toe injuries occur when the first metatarsophalangeal joint dorsiflexes beyond 56 degrees.…”
Section: Foot and Ankle Subcommitteementioning
confidence: 99%